Dynamic Analysis of Financial Ratios on Profitability: Evidence from Regional Development Banks in Central Java - Jatmiko, Bambang (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the effect of BOPO (Operational Efficiency Ratio), NPL (Non-Performing Loans), LDR (Loan to Deposit Ratio), KPMM (Capital Adequacy Ratio), and GWM (Statutory Reserves) on ROE (Return on Equity) in Regional Development Banks in Central Java. The research utilizes quarterly data from Q1 2017 to Q4 2024. The Partial Adjustment Model (PAM) is employed to capture the dynamic relationship between the variables. The results show that BOPO, KPMM, and GWM have a positive and significant relationship with ROE. Meanwhile, NPL also shows a positive effect on ROE, contrary to general expectations, indicating potential issues in risk management or profit compensation strategies. LDR has a negative but statistically insignificant impact on ROE. The adjustment coefficient of 0.83418 (1 0.16582) suggests that 83.41% of the gap between actual and expected ROE is corrected in each period. The findings imply that improving operational efficiency and maintaining adequate capital and reserve levels are key to enhancing profitability. Policymakers and bank management should also scrutinize the positive effect of NPLs on ROE, which may indicate unsustainable profit strategies or aggressive lending practices. This study contributes to the literature by applying the Partial Adjustment Model to regional banking performance in Indonesia, specifically over an extended post-pandemic period, offering fresh insights into how regional banks adjust their profitability in response to internal financial ratios and external regulatory pressures